Is the European Monetary Union an optimal currency area? : An empirical analysis of interest rate and inflation differentials across the Eurozone - Gúth, Ondřej (2015)
The economic crisis of 2008 had substantial impacts on the global economy. The European Monetary Union was affected as well, however, the economic impacts also stirred up political discussions concerning functioning of the European Union and its unity as divergence of economic means among the member countries intensified during the crisis. Inflation and real interest rate differentials have to substantial degree the ability to measure the divergence among the member countries of a monetary union. A number of empirical studies measuring the differentials in the Euro area were conducted since the start of the financial crisis in 2008. These studies show growing inflation and real interest rate differentials among the countries of the Euro area, argue that the European Monetary Union is becoming less stable and often question its future. This paper conducts similar empirical analysis; however, it differs from the above mentioned works of other authors by the larger time gap between the start of financial crisis and the time of conducting the analysis as it uses data until the year of 2013. This paper also contributes to current literature by the methodology it uses. The inflation and interest rate differentials in EMU are calculated by two methods and their results are subsequently compared, which has not been done before. The inflation and interest rate differentials are calculated for the USA as well in order to have an entity which can be considered as a hypothetical optimum currency area and to which the differentials of EMU could be compared. The results of the analysis in this paper will state whether the magnitude of inflation and interest rate differentials is too high and it will also either confirm the trend of divergence of inflation and real interest rates within the Euro area or show that this divergence is only a short-time period phenomenon of after-crisis years.